Identifying the underlying psychological constructs from self-expressed anti-vaccination argumentation - Holford, Dawn; Lopez-Lopez, Ezequiel; Fasce, Angelo; Karlsson, Linda C.; Lewandowsky, Stephan (Springer Nature, 2025)
People’s negative attitudes to vaccines can be motivated by psychological factors—such as fears, ideological beliefs, and cognitive patterns—known as ‘attitude roots’. This study had two primary objectives: (1) to identify which of 11 known attitude roots are featured in individuals’ self-expressed reasons for negative vaccine attitudes (i.e., a linguistic analysis); (2) to explore how attitude roots present in self-expressed texts are linked to specific psychological measures. To achieve Objective 1, our study collected data from December 2022 to January 2023 from 556 participants from the US, who wrote texts to explain the reasons for their negative vaccine attitudes. The texts encompassed 2327 conceptually independent units of anti-vaccination argumentation, that were each coded for its attitude root(s) by at least two psychological experts. By allowing participants to spontaneously express their attitudes in their own words, we were able to observe how this differed from what participants reported to endorse when presented with a list of arguments. We found that there were four groups of attitude roots based on linguistic similarity in self-expression. In addition, latent class analysis of participants’ coded texts identified three distinct groups of participants that were characterised by their tendency to express combinations of arguments related to (1) fears, (2) anti-scientific conceptions, and (3) politicised perspectives. To achieve Objective 2, we collected participants’ responses to 11 validated measures of psychological constructs expected to underlie the respective 11 attitude roots, and used a correlational design to investigate how participants’ self-expressed attitude roots were linked to these measures. Logistic regressions showed that an expected psychological construct was the strongest, and significant, predictor for expression of three out of the four attitude root groups. We discuss the implications of these findings for health communicators and practitioners.